ANÁLISE E DESENVOLVIMENTO DE CONVERSORES ESTÁTICOS PARA APLICAÇÕES DE MÉDIA TENSÃO - Rech, Cassiano; Salvadori, Fabiano; Bolacell, Julio C. O.; Campos, Maurício d.; Feyh, Andressa R. (Salão do Conhecimento, 2013)
Resumo